Association of bone mineral density with prediabetes risk among African-American and European-American adult offspring of parents with type 2 diabetes - Liu, Zhao; Asuzu, Peace; Patel, Avnisha; Wan, Jim; Dagogo-Jack, Sam (Frontiers in Endocrinology, 2023)
Introduction Type 2 diabetes mellitus (T2DM) is associated with alterations in bone mineral density (BMD), but association between prediabetes and BMD is unclear. Methods We analyzed BMD among the initially normoglycemic participants in the Pathobiology of Prediabetes in a Biracial Cohort (POP-ABC) study in relation to incident prediabetes during 5 years of follow-up. Results and Discussion A total of 343 participants (193 Black, 150 White) underwent DEXA during Year 1 of POP-ABC and were followed quarterly for 5 years. The mean age was 44.2 ± 10.6 years; BMI was 30.2 ± 7.23 kg/m2. At baseline, the mean BMD was 1.176 ± 0.135 g/cm2 (1.230 ± 0.124 g/cm2 in men vs. 1.154 ± 0.134 g/cm2 in women, P<0.0001; 1.203 ± 0.114 g/cm2 in Black vs. 1.146 ± 0.150 g/cm2 in White participants, P=0.0003). During 5 years of follow-up, 101 participants developed prediabetes and 10 subjects developed T2DM (progressors); 232 were nonprogressors. Progressors to prediabetes had numerically higher baseline BMD and experienced lower 1-year decline in BMD (P<0.0001) compared with nonprogressors. From Kaplan-Meier analysis, the time to 50% prediabetes survival was 2.15 y among participants in the lowest quartile of baseline BMD, longer than those in higher quartiles (1.31 – 1.41 y). Values for BMD correlated inversely with age and adiponectin levels, and positively with BMI. In logistic regression analysis, BMD z score significantly predicted incident prediabetes: more negative BMD z scores were associated with decreased incident prediabetes (odds ratio 0.598 [95% confidence interval 0.407 - 0.877], P=0.0085), after controlling for age, BMI, change in BMI, ethnicity, blood glucose and adiponectin. Conclusions Among initially normoglycemic individuals, higher baseline BMD was associated with higher risk of incident prediabetes during 5 years of follow-up.